Evaluating quality of life in patients with asthma and rhinitis: English adaptation of the Rhinasthma Questionnaire - Chen, Hubert (2011)
BACKGROUND: Separate health-related quality of life (HRQL) instruments exist for asthma and rhinitis. The Rhinasthma questionnaire, originally developed in Italian, is a unique measure designed for use where both conditions coexist. OBJECTIVE: We sought to assess the performance and validity of a new adaptation of the Rhinasthma for use in English-speaking populations. METHODS: We analyzed cross-sectional data from an ongoing study of adults with asthma and rhinitis (n=450), asthma alone (n=75), or rhinitis alone (n=20). Subjects were administered an English translation of the original 30-item Rhinasthma questionnaire. Health status measures simultaneously assessed include the Short Form (SF)-12, EuroQol (EQ)-5D, and Marks Asthma Quality-of-Life (AQoL). RESULTS: Variable cluster analysis of the original 30 item instrument identified 5 discrete item clusters corresponding to the following domains: nasal (5 items), eye (4 items), respiratory (5 items), activity restriction (9 items), treatment burden (5 items). Two other items were removed due to poor item-cluster correlations. Subjects with concomitant asthma and rhinitis had greater HRQL impairment, as measured by the Rhinasthma, than subjects with either asthma or rhinitis alone. The Rhinasthma correlated significantly (p<0.05) with the SF-12, EQ-5D, and Marks AQoL in the anticipated direction consistent with the underlying constructs. In multiple logistic regression, poorer Rhinasthma HRQL was associated with significantly (p<0.05) increased odds of both asthma- and rhinitis-related disability even after taking into account physical health status as measured by the SF-12. CONCLUSION: The 28-item English adaptation of Rhinasthma performs well in assessing HRQL in patients with asthma, rhinitis, or both conditions combined.